An attempt to assess the value of epidemiological structure of sexual networks in the detection of syphilis infection - Soszka-Jakubowska, Maria; Janczyło-Jankowska, Małgorzata; Jakubowski, Adam (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. Sociometric studies based on the evaluation of structures forming interpersonal network earned widespread recognition in sexually transmitted diseases (STD) epidemiology. Objective . The aim of this work is to assess the importance of epidemiological studies of infection sources, contacts and the network of connections created by them in the detection of early syphilis infections in the Bialystok province (1989–2010). Material and methods . Material for the study was the documentation of 316 patients diagnosed with early syphilis and 265 registered contacts declared by them, observed and treated in STD clinics. Epidemiological assessment was based on the basic parameters. Social Network Analysis was based on parameters of Seidman k-core. Results . Epidemiological studies showed that 67.4% of 316 patients with early syphilis reported registered contacts (index 0.83). 87.5% of these contacts have been tested and in more than a half (53%) of them early syphilis has been diagnosed. The remaining 16.8% of patients (with their consent) were subjected to prophylactic treatment, and the rest (after an appropriate time of control) were considered to be not infected. Thirty-three persons (12.5%) could not be found. Social Network Analysis of 316 patients showed that as many as 176 (53.7%) did not show any links in epidemiologic investigations. One hundred and twenty-two patients had 2–6 personal links without creating a k-core. Only in 1995, during a syphilis microepidemic (in town C), has a typical network of sexual relationships with a k-core consisting of 18 patients been revealed. Conclusions . The results of the study indicate major shortcomings in the work of STD clinics in Podlaskie Province in the years 1999–2010. Analysis of the structure of sexual networks is a valuable method for enriching the methodology of epidemiological investigations in detecting sources of infection and their contacts, provided very detailed epidemiological investigations are performed and there is close cooperation with other STD clinics. Social Network Analysis of infection sources and their sexual contacts allows forecasting the morbidity, as well as selecting groups according to their sexual behavior, regions in which infections may appear and patients’ social and ethnic group.